2019
DOI: 10.3389/fneur.2019.01270
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Unilateral Vestibular Perception in Adolescents With Idiopathic Scoliosis

Abstract: The cause of Adolescent Idiopathic Scoliosis (AIS) remains unclear, but one proposed cause of AIS is asymmetric vestibular function and the related descending drive to the spine musculature. The objective of this study was to determine if asymmetric vestibular function is present in individuals with AIS. Ten individuals with AIS (8F, 2M) and 10 healthy age- and sex-matched controls were exposed to 10s-long virtual rotations induced by monaural or binaural electrical vestibular stimulation (EVS), and 10s-long r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…These results are fully consistent with the findings of Gruber et al [18]; however, numerous studies have reported not only a greater COP range in the medial-lateral and anterior-posterior directions and sway area but also a greater sway path length in children/adolescents with scoliosis [5,10,12,19,20]. The enlarged values of spatial COP displacement parameters in both directions (medial-lateral and anterior-posterior occurring at normal excursions and COP velocity, as found in the present study) may result in large body oscillations in all directions and indicate decreased spatial postural stability in scoliosis patients [21,23]. Although there is no consensus in the literature on postural instability in scoliosis patients, our results are compatible with the results of most recent studies [12][13][14][15][16][17][18][19][20][21] as well as with the findings reported in both the latest systematic review and meta-analysis [23,27], which concluded that children and adolescents with IS were characterized by worse postural stability than healthy children were.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These results are fully consistent with the findings of Gruber et al [18]; however, numerous studies have reported not only a greater COP range in the medial-lateral and anterior-posterior directions and sway area but also a greater sway path length in children/adolescents with scoliosis [5,10,12,19,20]. The enlarged values of spatial COP displacement parameters in both directions (medial-lateral and anterior-posterior occurring at normal excursions and COP velocity, as found in the present study) may result in large body oscillations in all directions and indicate decreased spatial postural stability in scoliosis patients [21,23]. Although there is no consensus in the literature on postural instability in scoliosis patients, our results are compatible with the results of most recent studies [12][13][14][15][16][17][18][19][20][21] as well as with the findings reported in both the latest systematic review and meta-analysis [23,27], which concluded that children and adolescents with IS were characterized by worse postural stability than healthy children were.…”
Section: Discussionsupporting
confidence: 77%
“…A review of studies on postural stability in children/adolescents with scoliosis in comparison with their typically developing peers revealed that the results were not fully consistent. Notably, both earlier studies [ 8 , 9 , 10 ] as well as recent studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] reported significant differences in stability, while others reported a lack of differences in stability [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some evidence suggests that dysfunction of the vestibular system may be a contributing factor to the development of AIS 6 . Asymmetric vestibular function and the related descending drive to the spine musculature can lead to inappropriate trunk muscle activity, spine deformation, and greater instability 7 . On the other hand, several studies on adolescent patients with idiopathic scoliosis revealed their fair postural stability compared to the control group 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric vestibular information was also suggested to be the underlying cause of the abnormal sensory integration. Monaural and binaural vestibular stimulation showed altered balance control in patients with AIS [27] and larger functional vestibular asymmetry [28]. This asymmetry can be explained by unilateral abnormalities of the vestibular organs as was demonstrated by Carry [29] and Rousie [30].…”
Section: Discussionmentioning
confidence: 99%